The Influence of Taxpayer Knowledge, Motor Vehicle Tax Sanctions, and the Samsat Drive Thru System On Motor Vehicle Taxpayer Compliance (Case study of Motor Vehicle Taxpayer at Samsat Drive Thru Medan) - Berupilihen br Ginting; Adi Harianto; Mhd. Restu Razaq; Sabaruddin Chaniago; Amin Hou (Jurnal Ekonomi, 2024)
This study supposed to determine the effect of taxpayer knowledge, motor vehicle tax sanctions, and the Samsat Drive Thru system on compliance of motor vehicle taxpayers (case study of motor vehicle taxpayer at Samsat Drive Thru Medan). The type of research that will be used in this research is descriptive and associative methods, because there are variables that will be examined for their relationship and the aim is to present a structured, factual, and accurate description of the facts in the relationship between the variables studied. The population of this study is motor vehicle taxpayers who make PKB payments in 2023 and researchers limit the population to 150 taxpayers and the sampling technique used is accidental sampling of 150 taxpayers. The data analysis technique used is the Validity and reliability test to see the influence between variables using the Hypothesis test (Test and Test f) and the determination test using SPSS. The results showed that Taxpayer Knowledge has a positive and significant effect on Taxpayer Compliance at the Medan samsat office. PKB sanctions have a positive and significant effect on taxpayer compliance at the Medan samsat office. The Samsat Drive Thru system has a positive and significant effect on taxpayer compliance at the Medan samsat office. Determination Test Taxpayer Knowledge, motor vehicle tax sanctions Sanctions, Samsat Drive Thru system while the remaining 28.9% is influenced by other variables not examined in this study such as service quality, motor vehicle tax sanctions fees and other variables. To Dispenda as a government agency in charge of Motor Vehicle Tax payments should increase innovation in Motorized Tax payments as effectively and efficiently as possible so that taxpayer compliance will increase.